Introduction to the Raspberry Pi : single-board computing projects. - Barkstrom, Jeffrey (Apress, 2019)
"Discover ARM-based computing, system-on-a-board technologies, and how the Raspberry Pi is your gateway into SBC (single-board computing). In this video, you'll dive into all the different ways the Raspberry Pi can be used, such as for personal computing, acting as a server, IoT (internet of things) projects, robotics projects, monitor controllers, computer science experiments, digital signage, and super computers. You'll cover the various operating systems available for the Pi, the equipment needed to get started for the most popular types of projects and applications, and how to install and set everything up. With the introduction of the Raspberry Pi 4, the Raspberry Pi is now the most powerful system-on-a-board. This video shows you how to make the most of it."--Resource description page